Ziprasidone Therapy in the Acute Depressive Mixed State - Sinclair, Heather Q. (MD Conference Express, 2010)
Ziprasidone demonstrated efficacy and tolerability among patients with depressive mixed state, according to a recent study. In this double-blind, placebo-controlled, multicenter trial that included 74 patients who met DSM-IV criteria for major depressive disorder and two to three DSM-IV mania criteria, patients were randomized to receive either ziprasidone 40–160 mg/daily (n=36) or placebo (n=38) for 6 weeks in a forced titration regimen.